Method for manufacturing toner for electrostatic charge image development

The controlled temperature and solvent-free emulsification process for producing toner particles with colorant-containing polyester resin particles addresses uneven image density and thermal stability issues, ensuring consistent image quality and long-term storage.

JP2025008681APending Publication Date: 2025-01-20FUJIFILM BUSINESS INNOVATION CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023111047
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing toner manufacturing methods often result in image density unevenness and poor thermal storage properties due to uneven distribution of basic colorants and hydrolysis of polyester resins, which can lead to charge leakage and aggregation.

Method used

A method for producing toner particles by aggregating and coalescing colorant-containing polyester resin particles within a controlled temperature range (35°C to 100°C) and time-weighted average (200≦(T×lnR)≦550, using a solvent-free emulsification process to ensure uniform dispersion and prevent hydrolysis.

Benefits of technology

The method effectively suppresses image density unevenness and enhances thermal stability of the toner, maintaining consistent image quality and preventing aggregation over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008681000001
    Figure 2025008681000001
Patent Text Reader

Abstract

To provide a manufacturing method for manufacturing a toner for electrostatic charge image development which suppresses occurrence of image density unevenness and is excellent in heat storage property.SOLUTION: A method for manufacturing a toner for electrostatic charge image development includes aggregating and unifying material particles containing coloring agent-containing polyester resin particles in a dispersion medium and obtaining toner particles, and has a step of manufacturing coloring agent-containing polyester resin particles, wherein the step of manufacturing the coloring agent-containing polyester resin particles includes mixing a basic coloring agent and a polyester resin while imparting heat thereto and obtaining a mixture, and emulsifying the mixture, and in the step of manufacturing the coloring agent-containing polyester resin particles, a time weighted average T°C of a temperature of the polyester resin and a time R seconds in a period during which the temperature of the polyester resin is 35°C or higher and 100°C or lower satisfy a relation of 200≤(T×lnR)≤550.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a toner for developing electrostatic images. [Background technology]

[0002] Patent Document 1 discloses a dyed emulsion composition containing a dye and an emulsion polymer obtained by emulsion polymerizing a monomer mixture containing a vinyl monomer (A) having a cyano group, a vinyl monomer (B) having an acidic functional group, and other vinyl monomers (C) in the presence of an anionic surfactant (D). Patent Document 2 discloses a method for producing a toner, which includes: (A) a mixing step of mixing a binder resin containing a polyester having an acid group, a colorant, a basic substance, and a surfactant in an aqueous medium to obtain a mixture; (B) a melting and emulsifying step of applying a shearing force to the mixture while heating it to a temperature 10° C. or more higher than the softening temperature Tm of the binder resin to obtain a molten emulsion; (C) a cooling step of cooling the molten emulsion at a cooling rate of 0.5° C. / min to 10° C. / min to a temperature not higher than the glass transition temperature Tg of the binder resin while applying a shearing force to prepare a fine particle dispersion having a median diameter of 1.0 μm or less; and (D) a step of aggregating the fine particle dispersion in the aqueous medium. Patent Document 3 discloses resin microparticles containing a polyester resin and a basic dye, the resin microparticles having a volume average particle size of 0.05 μm or more and 1 μm or less, and a basic dye concentration ratio of the center of gravity of the resin microparticle to a surface portion at a depth of 10 nm or less from the surface of the resin microparticle of 0.8 or more. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-010846 A [Patent Document 2] JP 2010-276750 A [Patent Document 3] JP 2021-127428 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a method for producing a toner for developing electrostatic images, which suppresses the occurrence of uneven image density and has excellent heat storage properties. [Means for solving the problem]

[0005] Specific means for solving the above problems include the following aspects. <1> A method for producing a toner for developing an electrostatic image, comprising agglomerating and coalescing material particles including colorant-containing polyester resin particles in a dispersion medium to obtain toner particles, The colorant-containing polyester resin particles are produced the step of producing the colorant-containing polyester resin particles includes mixing a basic colorant and a polyester resin while applying heat to obtain a mixture, and emulsifying the mixture, In the production process of the colorant-containing polyester resin particles, a time-weighted average T°C of the temperature of the polyester resin and a time R seconds during which the temperature of the polyester resin is in the range of 35°C or more and 100°C or less satisfy the relationship of 200≦(T×lnR)≦550. A method for producing a toner for developing electrostatic images. <2> The temperature of the polyester resin is in the range of 35° C. or more and 100° C. or less throughout the entire production process of the colorant-containing polyester resin particles. <1> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <3> No organic solvent is used in the production process of the colorant-containing polyester resin particles. <1> or <2> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <4> The basic colorant comprises a basic dye; <1> ~ <3> 13. A method for producing the toner for developing electrostatic images according to claim 12. <5> The polyester resin includes an amorphous polyester resin. <1> ~ <4> 13. A method for producing the toner for developing electrostatic images according to claim 12. <6> a mass ratio of the basic colorant to the polyester resin contained in the colorant-containing polyester resin particles (basic colorant:polyester resin) is 0.1:99.9 to 20:80; <1> ~ <5> 13. A method for producing the toner for developing electrostatic images according to claim 12. <7> The colorant-containing polyester resin particles have a volume average particle size of 50 nm or more and 500 nm or less. <1> ~ <6> 13. A method for producing the toner for developing electrostatic images according to claim 12. <8> <1> ~ <7> 2. A toner for developing electrostatic images, which is produced by the method for producing a toner for developing electrostatic images according to claim 1. <9> <1> 8. An electrostatic image developer comprising a toner for developing electrostatic images produced by the method for producing a toner for developing electrostatic images according to any one of claims 1 to 7. Effect of the Invention

[0006] <1> , <2> , <3> , <4> , <5> , <6> or <7> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which suppresses the occurrence of uneven image density and has excellent heat storage properties, as compared with a case where the value of 200≦(T×lnR) is less than 200 or exceeds 550. <8> According to the present invention, there is provided a toner for developing electrostatic images which suppresses the occurrence of uneven image density and has excellent heat storage stability. <9> According to the present invention, there is provided an electrostatic image developer which suppresses the occurrence of uneven image density and has excellent heat storage properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0008] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0009] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved.

[0010] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0011] In the present disclosure, "(meth)acrylic" is an expression that includes both acrylic and methacrylic, and "(meth)acrylate" is an expression that includes both acrylate and methacrylate.

[0012] In this disclosure, "toner" refers to "toner for developing electrostatic images", "developer" refers to "electrostatic image developer", and "carrier" refers to "carrier for developing electrostatic images".

[0013] In the present disclosure, a method for producing toner particles by agglomerating and coalescing material particles in a dispersion medium is referred to as an EA (emulsion aggregation) method.

[0014] <Method of manufacturing toner for developing electrostatic images> The toner production method according to this embodiment is a toner production method that includes producing toner particles by the EA method.

[0015] In the toner manufacturing method according to the present embodiment, at least colorant-containing polyester resin particles are used as material particles. Therefore, the method for producing the toner according to this embodiment includes aggregating and coalescing material particles including colorant-containing polyester resin particles in a dispersion medium to obtain toner particles.

[0016] Specifically, the method for producing the toner according to the present embodiment includes the following steps: The method includes the steps of: The process for producing colorant-containing polyester resin particles includes mixing a basic colorant and a polyester resin while applying heat to obtain a mixture, and emulsifying the mixture, In the manufacturing process of colorant-containing polyester resin particles, the time-weighted average T°C of the temperature of the polyester resin and the time R seconds during which the temperature of the polyester resin is in the range of 35°C or more and 100°C or less satisfy the relationship 200≦(T×lnR)≦550.

[0017] In the manufacturing process of the colorant-containing polyester resin particles, the temperature of the polyester resin may be constant or may fluctuate. When the temperature of the polyester resin fluctuates, there may be a time period when the temperature is less than 35° C. or a time period when the temperature is more than 100° C., but the temperature of the polyester resin is preferably in the range of 35° C. or more and 100° C. or less throughout the manufacturing process of the colorant-containing polyester resin particles. The time-weighted average temperature T° C. of the polyester resin is the average temperature of the polyester resin during the production process of the colorant-containing polyester resin particles, weighted by the time during which that temperature continued. lnR is the natural logarithm of R.

[0018] According to the toner manufacturing method of the present embodiment, a toner that suppresses the occurrence of uneven image density and has excellent heat storage properties is manufactured. The mechanism by which this occurs is assumed to be as follows.

[0019] The EA method is known as a method for stably producing toner particles with a particle size of several μm. However, depending on the type of material used in the EA method, it may be difficult for the material particles to disperse uniformly with each other, and a specific material may become unevenly distributed inside the toner particles as clumps. In toners and developers containing such toner particles, charge leakage is likely to occur, and image density unevenness may occur. For example, when polyester resin particles and basic colorant particles are used as material particles in the EA method, the basic colorant may become unevenly distributed inside the toner particles as clumps, causing image density unevenness. In the present embodiment, as a measure to suppress the above phenomenon, the basic colorant particles, which are material particles for the EA method, are made to contain not only a basic colorant but also a polyester resin, thereby suppressing the basic colorant from being unevenly distributed in the form of clumps inside the toner particles. In this embodiment, the temperature and heating time to which the polyester resin is exposed are controlled in the manufacturing process of the colorant-containing polyester resin particles. The polyester resin is easily hydrolyzed by the action of the basic colorant, but the hydrolysis of the polyester resin is suppressed by controlling the temperature and time of the manufacturing process of the colorant-containing polyester resin particles. As a result, the molecular weight of the polyester resin is maintained, and the toner is less likely to aggregate even if the toner is left at high temperatures for a long period of time after production.

[0020] In the manufacturing process of colorant-containing polyester resin particles, from the viewpoint of increasing the dispersibility of the basic colorant, it is preferable that the temperature of the dispersion liquid during granulation is high. On the other hand, the higher the temperature of the dispersion liquid during granulation, the more easily the hydrolysis of the polyester resin proceeds. In the manufacturing process of colorant-containing polyester resin particles, the present embodiment controls the time-weighted average T°C of the temperature of the polyester resin and the time R seconds during which the temperature of the polyester resin is in the range of 35°C to 100°C so as to satisfy the relationship 200≦(T×lnR)≦550.

[0021] If (T×lnR) is less than 200, the basic dye is insufficiently dispersed in the polyester resin, which may result in uneven image density. In order to suppress this phenomenon, (T×lnR) is 200 or more, preferably 250 or more, and more preferably 300 or more. If (T×lnR) exceeds 550, hydrolysis of the polyester resin proceeds, and the heat-resistant storage stability of the toner after production may deteriorate. From the viewpoint of suppressing this phenomenon, (T×lnR) is 550 or less, preferably 500 or less, and more preferably 450 or less.

[0022] From the viewpoint of controlling (T×lnR) within the above range, the temperature of the polyester resin throughout the entire production process of the colorant-containing polyester resin particles is preferably in the range of 35° C. or higher and 100° C. or lower, more preferably in the range of 38° C. or higher and 98° C. or lower, and even more preferably in the range of 40° C. or higher and 95° C. or lower.

[0023] In the present embodiment, the production of toner particles by the EA method is specifically carried out as follows: an aggregating step of aggregating material particles in a dispersion liquid containing the material particles to form aggregated particles; and a coalescence step of heating the dispersion liquid containing the aggregated particles to fuse and coalesce the aggregated particles to form toner particles. The material particles include colorant-containing polyester resin particles that contain a basic colorant and a polyester resin.

[0024] The process for producing the colorant-containing polyester resin particles, the steps of the EA method, and materials in this embodiment will be described in detail below.

[0025] [Production process of colorant-containing polyester resin particles] The process for producing the colorant-containing polyester resin particles includes mixing a basic colorant and a polyester resin while applying heat to obtain a mixture, and emulsifying the mixture.

[0026] From the viewpoint of making the basic colorant easily uniformly present inside the colorant-containing polyester resin particles and inside the toner particles, the mass ratio of the basic colorant to the polyester resin contained in the colorant-containing polyester resin particles is preferably basic colorant:polyester resin=0.1:99.9 to 20:80, more preferably 0.5:99.5 to 15:85, and even more preferably 1:99 to 10:90.

[0027] The colorant-containing polyester resin particles preferably have a volume average particle size of 50 nm to 500 nm, more preferably 65 nm to 400 nm, and even more preferably 80 nm to 300 nm, from the viewpoint of uniform dispersion and aggregation in the aggregation step of the EA method. The volume average particle size of colorant-containing polyester resin particles refers to the particle size that is 50% cumulative from the small diameter side in the particle size distribution measured with a laser diffraction particle size distribution analyzer (e.g., model number: LS13-320, Beckman Coulter). The number of particles measured is 10,000.

[0028] -Basic colorants- The basic colorant may be used alone or in combination of two or more kinds. The basic colorant may be a basic dye or a basic pigment. As the basic colorant, only a basic dye may be used, only a basic pigment may be used, or a basic dye and a basic pigment may be used in combination. The basic colorant may be a fluorescent colorant. As the basic colorant, only a non-fluorescent colorant may be used, only a fluorescent colorant may be used, or a non-fluorescent colorant and a fluorescent colorant may be used in combination.

[0029] Examples of basic dyes include diazine dyes, oxazine dyes, thiazine dyes, azo dyes, anthraquinone dyes, xanthene dyes, triarylmethane dyes, phthalocyanine dyes, auramine dyes, acridine dyes, and methine dyes. Specific examples of the dyes include the following: Diazine dyes such as Basic Red 2, 5, 6, 10, Basic Blue 13, 14, 16, Basic Violet 5, 6, 8, 12, Basic Yellow 14; oxazine dyes such as Basic Blue 3, 6, 10, 12, 74; thiazine dyes such as Basic Blue 9, 17, 24, 25, Basic Green 5; Basic Red 18, 22, 23, 24, 29, 30, 31, 32, 34, 38, 39, 46, 51, 53, 54, 55, 62, 64, 76, 94, 111, 118, Basic Blue 41, 53, 54, 55, 64, 65, 66, 67, 162, Basic Violet 18, 36, Basic Yellow Azo dyes such as 15, 19, 24, 25, 28, 29, 38, 39, 49, 51, 57, 62, 73, Basic Orange 1, 2, 24, 25, 29, 30, 33, 54, 69; anthraquinone dyes such as Basic Blue 22, 44, 47, 72; xanthene dyes such as Basic Red 1, 1:1, 3, 4, 8, 11, Basic Violet 10, 11, 11:1; triarylmethane dyes such as Basic Red 9, Basic Blue 1, 2, 5, 7, 8, 11, 15, 18, 20, 23, 26, 35, 81, Basic Violet 1, 2, 3, 4, 14, 23, Basic Green 1, 4; phthalocyanine dyes such as Basic Blue 140; auramine dyes such as Basic Yellow 2, 3, 37; Basic Yellow acridine dyes such as Basic Red 12, 13, 14, 15, 27, 28, 37, 52, 90, Basic Yellow 11, 13, 20, 21, 52, 53, Basic Orange 21, 22, and Basic Violet 7, 15, 16, 20, 21, 22.

[0030] Examples of basic pigments include azo pigments and quinacridone pigments. Specific examples of the basic pigments include the following pigments. Azo pigments such as Pigment Red 146, 166, Pigment Yellow 1, 13, 74, 83, and 180; quinacridone pigments such as Pigment Orange 48, 49, Pigment Red 122, 202, 206, 207, 209, and Pigment Violet 19.

[0031] As the fluorescent basic colorant, from the viewpoint of fluorescence intensity, Basic Red 1 (Rhodamine 6G), Basic Red 1:1, Basic Red 2, Basic Red 12, Basic Red 13, Basic Red 14, Basic Red 15, Basic Red 36, Basic Violet 7, Basic Violet 10 (Rhodamine B), Basic Violet 11 (Rhodamine 3B), Basic Violet 11:1 (Rhodamine A), Basic Violet 15, Basic Violet 16, Basic Violet 27, Basic Yellow 1, Basic Yellow 2, Basic Yellow 9, Basic Yellow 24, Basic Yellow 40, Basic Orange 15, Basic Orange 22, Basic Blue 1, Basic Blue 3, Basic Blue 7, Basic Blue 9, Basic Blue 45, and Basic Green 1 are preferable, and Basic Red 1 (Rhodamine 6G), Basic Red 1:1, Basic Red 2, Basic Red 12, and Basic Red More preferred are Basic Red 13, Basic Red 14, Basic Red 15, Basic Red 36, Basic Violet 7, Basic Violet 10 (Rhodamine B), Basic Violet 11 (Rhodamine 3B), Basic Violet 11:1 (Rhodamine A), Basic Violet 15, Basic Violet 16, and Basic Violet 27.

[0032] -Polyester resin- The polyester resin may be an amorphous polyester resin or a crystalline polyester resin. The polyester resin may be an amorphous polyester resin alone, a crystalline polyester resin alone, or a combination of an amorphous polyester resin and a crystalline polyester resin. The polyester resin is preferably an amorphous polyester resin.

[0033] -Amorphous polyester resin- The amorphous polyester resin may be a commercially available product or a synthetic product. The amorphous polyester resin may be, for example, a condensation polymer of a polycarboxylic acid and a polyhydric alcohol.

[0034] Examples of polyvalent carboxylic acids that are polymerization components of amorphous polyester resins include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, or lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferred as the polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0035] Examples of polyhydric alcohols that are polymerization components of amorphous polyester resins include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,1 Examples of the polyhydric alcohol include 1-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol, alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, and hydrogenated bisphenol A), and aromatic diols (e.g., an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A). Among these, the polyhydric alcohol is preferably an aliphatic diol. As the polyhydric alcohol which is a polymerization component of the amorphous polyester resin, a polyhydric alcohol having a crosslinked structure or a branched structure of trihydric or more may be used in combination with the diol. Examples of the polyhydric alcohol having trihydric or more include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0036] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or more and 75°C or less, more preferably 50°C or more and 70°C or less, and even more preferably 50°C or more and 65°C or less. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0037] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0038] The acid value of the amorphous polyester resin is preferably from 1 mgKOH / g to 50 mgKOH / g, more preferably from 3 mgKOH / g to 30 mgKOH / g, and further preferably from 5 mgKOH / g to 18 mgKOH / g. The acid value of the amorphous polyester resin is determined by the neutralization titration method specified in JIS K0070-1992 using an appropriate amount of the amorphous polyester resin as a sample.

[0039] The amorphous polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0040] -Crystalline polyester resin- The crystalline polyester resin may be a commercially available product or a synthetic product. Examples of the crystalline polyester resin include polycondensates of polyvalent carboxylic acids and polyhydric alcohols. The crystalline polyester resin is preferably a polycondensate of a linear aliphatic polymerizable monomer rather than a polymerizable monomer having an aromatic ring, since it easily forms a crystal structure.

[0041] Examples of polyvalent carboxylic acids that are polymerization components of crystalline polyester resins include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower (e.g., carbon number 1 to 5) alkyl esters. As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0042] Examples of polyhydric alcohols that are polymerization components of crystalline polyester resins include aliphatic diols (for example, straight-chain aliphatic diols having a main chain carbon number of 7 to 20). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. As the polyhydric alcohol which is a polymerization component of the crystalline polyester resin, a trihydric or higher alcohol having a crosslinked or branched structure may be used in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0043] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" as described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0044] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0045] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester.

[0046] The colorant-containing polyester resin particles are preferably produced in the form of a dispersion liquid containing the particles. That is, the process for producing the colorant-containing polyester resin particles is preferably a process for producing a colorant-containing polyester resin particle dispersion liquid. From the viewpoint of containing a sufficient amount of colorant in the toner particles, the solid content concentration of the colorant-containing polyester resin particle dispersion is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more. The solid content concentration of the colorant-containing polyester resin particle dispersion is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, from the viewpoint of particle dispersibility.

[0047] Hereinafter, "solvent-free emulsification" and "solvent emulsification" will be described as examples of the process for producing colorant-containing polyester resin particles. In the solvent-free emulsification and solvent emulsification, a colorant-containing polyester resin particle dispersion is produced.

[0048] -Solvent-free emulsion- Solvent-free emulsification is a method in which no organic solvent is used in the production process of colorant-containing polyester resin particles. Specifically, the solvent-free emulsification is a melting step of mixing a basic colorant, a polyester resin, a basic compound (excluding the basic colorant), and a surfactant by applying heat and shear force to obtain a mixture in which the basic colorant is dispersed in the molten polyester resin; and an emulsification step of adding an aqueous medium to the mixture while applying a shear force to the mixture to emulsify it.

[0049] In solventless emulsification, the time-weighted average of temperature, T°C, and time, R seconds, refers to the temperature, T°C, and time, R seconds, from the start of the melting step to the end of the emulsification step.

[0050] In the solventless emulsification, the melting step and the emulsification step are preferably carried out using a kneading extruder. The kneading extruder is a device that applies heat and shear force to the material to be treated while continuously conveying the material. The structure of the kneading extruder is generally roughly divided into a material inlet, a barrel, and a die from upstream to downstream. A screw is provided inside the barrel. A heater for heating the inside of the barrel is provided around the barrel. The screw may be a single-screw type or a twin-screw type, and the twin-screw type is preferable.

[0051] As the basic compound, sodium hydroxide or potassium hydroxide is suitable. From the viewpoint of uniformity of kneading, sodium hydroxide or potassium hydroxide is preferably used in the form of an aqueous solution (i.e., an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution).

[0052] The amount of the basic compound used is an amount that can emulsify and disperse the mixture. Specifically, the amount of the basic compound used is preferably an amount that results in a neutralization rate of 30% or more and 80% or less according to the following formula (1). Formula (1): Neutralization rate (%) = mb×n×56.1÷Mwb÷AV×1000, mb is the amount (g) of basic compound used per 1 g of polyester resin, n is the valence of the basic compound, Mwb is the molecular weight of the basic compound, AV is the acid value of the polyester resin (mg KOH / g).

[0053] The surfactant may be any of anionic surfactants, cationic surfactants, and nonionic surfactants. Examples include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The surfactants may be used alone or in combination of two or more. The nonionic surfactants may be used in combination with an anionic surfactant or a cationic surfactant. The amount of surfactant used is an amount that allows the emulsified particles to remain dispersed.

[0054] The aqueous medium is preferably water with a reduced ion content, such as distilled water or ion-exchanged water. The aqueous medium is preferably used at a temperature adjusted to a range of 35° C. to 100° C., and more preferably within a range of ±5° C. of the internal barrel temperature of the kneading extruder.

[0055] The temperature inside the barrel of the kneading extruder in the melting step is preferably 80°C or higher and 110°C or lower, more preferably 85°C or higher and 105°C or lower, and even more preferably 90°C or higher and 100°C or lower. The temperature inside the barrel of the kneading extruder in the emulsification step is preferably 80°C or higher and 110°C or lower, more preferably 85°C or higher and 105°C or lower, and even more preferably 90°C or higher and 100°C or lower.

[0056] When using a twin-screw extruder, the average feed rate of the mixture from the melting process to the emulsification process is 0.15kg / (h cm) obtained by dividing the feed rate (kg / h) by the cube of the shaft diameter (cm). 3 ) or more 3.0kg / (h cm 3 ) or less is preferable, and 0.5kg / (h cm 3 ) or more 2.5kg / (h cm 3 ) or less is preferable, and 0.8kg / (h cm 3 ) or more 2.0kg / (h cm 3 ) The following is more preferred.

[0057] The L / D (ratio of screw length L to screw diameter D) of the kneading extruder is preferably 30 to 90, more preferably 40 to 80, and even more preferably 50 to 70, throughout the melting and emulsifying steps.

[0058] -Solvent emulsification- Specifically, the solvent emulsification is a dissolving step of mixing a basic colorant, a polyester resin, and an organic solvent in which the polyester resin is soluble while applying heat to dissolve the polyester resin in the organic solvent and dissolve or disperse the basic colorant in the organic solvent to obtain a mixture; and an emulsification step of adding a basic compound to the mixture, and then adding an aqueous medium to disperse the mixture in the aqueous medium in the form of particles.

[0059] In solvent emulsification, the time-weighted average of temperature, T°C, and time, R seconds, refers to the temperature, T°C, and time, R seconds, from the start of the dissolution step to the end of the emulsification step.

[0060] The solvent emulsification is preferably carried out in a stirring tank equipped with a stirring means and a heating / cooling means for the dissolving step and the emulsifying step. The stirring means is preferably a stirring means having a rotating shaft and a stirring blade. The heating / cooling means is preferably a means for applying and / or removing heat from the wall surface of the stirring tank.

[0061] Examples of organic solvents in which polyester resins are soluble include ethyl acetate, isopropanol, 2-butanol, methyl ethyl ketone, and mixed solvents thereof. Among these, organic solvents or mixed solvents having a boiling point of 60° C. or higher and lower than 100° C. are preferred.

[0062] The basic compound is preferably ammonia water.

[0063] The amount of the basic compound used is an amount that can emulsify and disperse the mixture. Specifically, the amount of the basic compound used is preferably an amount that results in a neutralization rate of 50% or more and 100% or less according to the following formula (1). Formula (1): Neutralization rate (%) = mb×n×56.1÷Mwb÷AV×1000, mb is the amount (g) of basic compound used per 1 g of polyester resin, n is the valence of the basic compound, Mwb is the molecular weight of the basic compound, AV is the acid value of the polyester resin (mg KOH / g).

[0064] The aqueous medium is preferably water with a reduced ion content, such as distilled water or ion-exchanged water. The aqueous medium is preferably used at a temperature adjusted to a range of 35° C. to 100° C. (preferably 35° C. to 55° C.).

[0065] The temperature of the material to be treated contained in the stirring tank during the dissolving step is preferably 25°C or higher and 60°C or lower, more preferably 30°C or higher and 55°C or lower, and even more preferably 35°C or higher and 50°C or lower. The temperature of the material to be treated contained in the stirring tank during the emulsification step is preferably 25°C or higher and 60°C or lower, more preferably 30°C or higher and 55°C or lower, and even more preferably 35°C or higher and 50°C or lower.

[0066] The method of adding the aqueous medium in the emulsification step is preferably dropwise. The time for dropping a specified amount of the aqueous medium (twice the amount of the resin) in the emulsification step is preferably from 10 to 150 minutes, more preferably from 20 to 140 minutes, and even more preferably from 30 to 130 minutes.

[0067] After the addition of the aqueous medium is completed, it is preferable to reduce the pressure inside the stirring tank and / or bubble the emulsion to remove the organic solvent. Thereafter, a surfactant may be added to improve the dispersion stability of the particles. Examples of the surfactant include the anionic surfactant, cationic surfactant, and nonionic surfactant described above.

[0068] [Manufacturing processes for other material particles] Other material particles include binder resin particles and release agent particles. The binder resin particles are preferably produced in the form of a dispersion containing the binder resin particles. The release agent particles are preferably produced in the form of a dispersion containing the release agent particles. Hereinafter, the binder resin particle dispersion liquid and the release agent particle dispersion liquid will be collectively referred to as "particle dispersion liquid" to describe what they have in common.

[0069] An example of an embodiment of a particle dispersion liquid is a dispersion liquid in which a material is dispersed in the form of particles in a dispersion medium by a surfactant.

[0070] The dispersion medium of the particle dispersion liquid is preferably an aqueous medium. Examples of the aqueous medium include water and alcohol. The water is preferably water with a reduced ion content, such as distilled water or ion-exchanged water. These aqueous media may be used alone or in combination of two or more.

[0071] The surfactant for dispersing the material in the dispersion medium may be any of anionic surfactants, cationic surfactants, and nonionic surfactants. Examples of such surfactants include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The surfactants may be used alone or in combination of two or more. The nonionic surfactants may be used in combination with an anionic surfactant or a cationic surfactant.

[0072] Methods for dispersing a material in a particulate form in a dispersion medium include known dispersion methods using a rotary shear type homogenizer, a ball mill having media, a sand mill, a dyno mill, and the like.

[0073] A method for dispersing a resin in a dispersion medium in the form of particles includes the phase inversion emulsification method. One example of the phase inversion emulsification method is a method in which a resin is dissolved in a hydrophobic organic solvent in which the resin is soluble, a basic compound is added to the organic continuous phase (O phase), and then an aqueous medium (W phase) is added to invert the phase from W / O to O / W, thereby dispersing the resin in the form of particles in the aqueous medium.

[0074] The volume average particle size of the particles dispersed in the particle dispersion is preferably 30 nm or more and 300 nm or less, more preferably 50 nm or more and 250 nm or less, and even more preferably 80 nm or more and 200 nm or less. The volume average particle size of particles in a particle dispersion refers to the particle size that is 50% cumulative from the smallest diameter side in the particle size distribution measured with a laser diffraction particle size distribution analyzer (e.g., model number: LS13-320, Beckman Coulter). The number of particles measured is 10,000.

[0075] The content of particles contained in the particle dispersion is preferably from 5% by mass to 50% by mass, more preferably from 10% by mass to 40% by mass, and even more preferably from 15% by mass to 30% by mass.

[0076] The materials constituting the particles of each of the binder resin particle dispersion liquid and the release agent particle dispersion liquid will be described below.

[0077] -Binding resin- Examples of the binder resin include homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or vinyl resins made of copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.

[0078] As the binder resin, a polyester resin is suitable. Examples of the polyester resin include an amorphous polyester resin and a crystalline polyester resin. As the polyester resin, only an amorphous polyester resin may be used, only a crystalline polyester resin may be used, or an amorphous polyester resin and a crystalline polyester resin may be used in combination.

[0079] When an amorphous polyester resin is used in producing the colorant-containing polyester resin particles, it is preferable that the binder resin contains an amorphous polyester resin having the same morphology as the amorphous polyester resin. When a crystalline polyester resin is used in the production of the colorant-containing polyester resin particles, it is preferable that the binder resin contains a crystalline polyester resin having the same form as the crystalline polyester resin.

[0080] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0081] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0082] [Aggregation step (first aggregation step)] The aggregating step is a step of aggregating material particles in a dispersion liquid containing the material particles to form aggregated particles.

[0083] The dispersion liquid to be subjected to the aggregation step contains at least colorant-containing polyester resin particles. The dispersion liquid to be subjected to the aggregation step preferably also contains binder resin particles and release agent particles.

[0084] When the toner manufacturing method according to the present embodiment includes a second aggregation step (a step for forming a shell) described later, the above aggregation step is referred to as a "first aggregation step." The first aggregation step is a step for forming a core in a toner having a core-shell structure.

[0085] The dispersion liquid to be subjected to the aggregation step is prepared, for example, by preparing a colorant-containing polyester resin particle dispersion liquid, a binder resin particle dispersion liquid, and a release agent particle dispersion liquid, and mixing these particle dispersion liquids. The order in which these particle dispersion liquids are mixed is not limited. Hereinafter, a dispersion liquid obtained by mixing a plurality of types of particle dispersion liquids is referred to as a "mixed dispersion liquid."

[0086] The mass ratio of the particles contained in the mixed dispersion is preferably in the following range. The mass ratio of the binder resin particles to the colorant-containing polyester resin particles (binder resin particles:colorant-containing polyester resin particles) is preferably 100:1 to 100:100, more preferably 100:2 to 100:60, and even more preferably 100:5 to 100:40. The mass ratio of the binder resin particles to the release agent particles is preferably 100:1 to 100:40, more preferably 100:2 to 100:30, and even more preferably 100:5 to 100:20.

[0087] After mixing the multiple types of particle dispersions, it is preferable to adjust the pH of the mixed dispersion to a range of 3 to 4. Examples of a means for adjusting the pH of the mixed dispersion include the addition of an acidic aqueous solution such as a nitric acid aqueous solution, a hydrochloric acid aqueous solution, or a sulfuric acid aqueous solution.

[0088] The aggregation step may, for example, be adding a flocculant to the mixed dispersion while stirring the mixed dispersion; After adding the flocculant to the mixed dispersion, the mixed dispersion is heated while being stirred to increase the temperature of the mixed dispersion.

[0089] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. The flocculant may be used alone or in combination of two or more kinds.

[0090] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0091] The flocculant is preferably a divalent or higher metal salt compound, more preferably a trivalent metal salt compound, and even more preferably a trivalent inorganic aluminum salt compound, such as aluminum chloride, aluminum sulfate, polyaluminum chloride, and polyaluminum hydroxide.

[0092] The amount of the flocculant to be added is not limited. When a trivalent metal salt compound is used as the flocculant, the amount of the trivalent metal salt compound to be added is preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.05 parts by mass or more and 5 parts by mass or less, and even more preferably 0.1 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0093] The temperature that the mixed dispersion reaches when it is heated is preferably a temperature based on the glass transition temperature (Tg) of the binder resin particles, for example, from (Tg-30°C) to (Tg°C) of the binder resin particles. When the mixed dispersion contains a plurality of types of binder resin particles having different Tg's, the lowest temperature among the Tg's is set as the Tg in the aggregation step.

[0094] [Second flocculation step] The second aggregation step is a step for the purpose of producing a toner having a core-shell structure, and is a step performed after the first aggregation step. The second aggregation step is a step for forming a shell.

[0095] The second aggregation step is a step of mixing a dispersion liquid containing aggregated particles with a dispersion liquid containing resin particles that will form the shell, and aggregating the resin particles that will form the shell onto the surfaces of the aggregated particles to form second aggregated particles.

[0096] As the dispersion liquid containing the resin particles that will become the shell, at least one selected from binder resin particle dispersion liquids for forming the core is suitable, a polyester resin particle dispersion liquid is more suitable, and an amorphous polyester resin particle dispersion liquid is even more suitable.

[0097] The second aggregation step may, for example, adding a dispersion liquid containing resin particles to be a shell to the dispersion liquid containing the aggregated particles while stirring the dispersion liquid containing the aggregated particles; and heating, while stirring, the dispersion liquid containing the aggregated particles after the dispersion liquid containing the resin particles that will become the shell has been added.

[0098] When the dispersion liquid containing the aggregated particles is heated, the temperature that the dispersion liquid containing the aggregated particles reaches is preferably a temperature based on the glass transition temperature (Tg) of the resin particles that form the shell, for example, a temperature not lower than (Tg-30°C) and not higher than (Tg-10°C) of the resin particles that form the shell.

[0099] After the aggregated particles or the second aggregated particles have grown to a predetermined size, a chelating agent for the aggregating agent used in the aggregation step may be added to the dispersion containing the aggregated particles or the second aggregated particles in order to stop the growth of the aggregated particles or the second aggregated particles before the heating in the coalescence step is performed. Examples of the chelating agent include oxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; and aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA). The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the binder resin particles.

[0100] After the aggregated particles or the second aggregated particles have grown to a predetermined size, the pH of the dispersion containing the aggregated particles or the second aggregated particles may be increased in order to stop the growth of the aggregated particles or the second aggregated particles before the heating in the coalescence step is performed. The means for increasing the pH of the dispersion containing the aggregated particles or the second aggregated particles includes the addition of at least one selected from the group consisting of an aqueous solution of an alkali metal hydroxide and an aqueous solution of an alkaline earth metal hydroxide. The ultimate pH of the dispersion containing the aggregated particles or the second aggregated particles is preferably 8 or more and 10 or less.

[0101] [Combining process] The coalescence step is a step in which the dispersion liquid containing the aggregated particles is heated to fuse and coalesce the aggregated particles to form toner particles.

[0102] When the second aggregation step is performed before the coalescence step, the coalescence step is a step in which the dispersion liquid containing the second aggregated particles is heated to fuse and coalesce the second aggregated particles to form toner particles. By performing the second aggregation step and the coalescence step, toner particles having a core-shell structure can be produced.

[0103] The form described below is common to the aggregated particles and the second aggregated particles.

[0104] The temperature reached by the dispersion liquid containing the aggregated particles is preferably equal to or higher than the glass transition temperature (Tg) of the binder resin, and specifically, is preferably 10° C. to 30° C. higher than the Tg of the binder resin. When the aggregated particles contain a plurality of binder resins having different Tg's, the highest temperature among the Tg's is defined as the glass transition temperature in the coalescence step.

[0105] After the coalescence step, the toner particles in the dispersion are subjected to a known washing step, solid-liquid separation step, and drying step to obtain dried toner particles. In the washing step, from the viewpoint of chargeability, it is preferable to carry out sufficient substitution washing with ion-exchanged water. In the solid-liquid separation step, it is preferable to carry out suction filtration, pressure filtration, etc., from the viewpoint of productivity. In the drying step, it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc., from the viewpoint of productivity.

[0106] [Step of adding external additives] The method for producing the toner according to the present embodiment preferably includes a step of externally adding an external additive to the toner particles. The external additive is added to the toner particles by mixing the toner particles in a dry state with the external additive. The mixing is performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.

[0107] Examples of the external additive include inorganic particles. Examples of inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, and K2O·(TiO2). n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0108] The surface of the inorganic particles as an external additive may be subjected to hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0109] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.

[0110] The amount of the external additive added is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2% by mass, based on the mass of the toner particles.

[0111] <Toner for developing electrostatic images> The toner produced by the production method according to the present embodiment is preferably an externally added toner in which an external additive is added to toner particles. The form of the external additive is as described above.

[0112] The toner particles contain at least a polyester resin and a basic colorant. The toner particles may contain a binder resin other than the polyester resin. The toner particles may contain a release agent.

[0113] The total content of the polyester resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the entire toner.

[0114] When the toner particles contain a crystalline polyester resin, the content of the crystalline polyester resin is preferably from 3% by mass to 30% by mass, and more preferably from 8% by mass to 20% by mass, of the total binder resin.

[0115] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner.

[0116] The content of the basic colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner.

[0117] The volume average particle diameter of the toner is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm. The method for measuring the volume average particle diameter of the toner is as follows. The particle size distribution of the toner is measured using a Coulter Multisizer II (manufactured by Beckman Coulter) and an electrolyte ISOTON-II (manufactured by Beckman Coulter). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% by mass aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant. This is added to 100 ml to 150 ml of electrolyte. The electrolyte in which the sample is suspended is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture of 100 μm diameter. The number of particles measured is 50,000. The particle size distribution is plotted from the small diameter side, and the particle size at which the cumulative 50% is determined as the volume average particle size D50v.

[0118] The average circularity of the toner is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less. The average circularity of the toner is calculated by dividing the perimeter of a circle having the same area as the projected image of a particle by the perimeter of the projected image of a particle. It is determined by measuring 3,500 particles using a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation).

[0119] <Developer> The toner produced by the production method according to the present embodiment may be used as a one-component developer, or may be mixed with a carrier and used as a two-component developer.

[0120] The carrier is not particularly limited, and may be any known carrier. Examples of the carrier include a coated carrier in which the surface of a core material made of magnetic powder is coated with a resin, a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin, and a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersion type carrier or the resin-impregnated type carrier may be a carrier in which the constituent particles of the carrier serve as a core material, and the surface of the core material is coated with a resin.

[0121] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.

[0122] Examples of the resin and matrix resin for coating include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, acrylic acid ester copolymer, styrene-acrylic acid ester copolymer, resin having a cycloalkyl group, acrylic acid ester copolymer having a cycloalkyl group, straight silicone resin or its modified product comprising an organosiloxane bond, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. Acrylic acid ester copolymer, styrene-acrylic acid ester copolymer, resin having a cycloalkyl group, acrylic acid ester copolymer having a cycloalkyl group are preferred. The resin and matrix resin for coating may contain other additives such as conductive particles. Examples of the conductive particles include metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0123] To coat the surface of the core material with a resin, a method of coating with a coating layer forming solution in which the coating resin and various additives (used as necessary) are dissolved in a suitable solvent can be mentioned. The solvent is not particularly limited and may be selected taking into consideration the type of resin used, suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer; a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material; a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air; and a kneader coater method in which the carrier core material and the solution for forming a coating layer are mixed in a kneader coater and then the solvent is removed.

[0124] The mixture ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100. EXAMPLES

[0125] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are by mass. In the following description, unless otherwise specified, synthesis, production, processing, measurement, etc. were carried out at room temperature (25° C.±3° C.).

[0126] <Preparation of amorphous polyester resin (A)> The following materials were prepared: Terephthalic acid: 30 parts by mole Fumaric acid: 70 parts by mole Bisphenol A ethylene oxide adduct: 5 mole parts Bisphenol A propylene oxide adduct: 95 parts by mole

[0127] The above materials were charged into a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature of the reaction solution was raised to 220°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature of the reaction solution was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while maintaining the temperature of the reaction solution at 230°C. The temperature of the reactant was then cooled to room temperature. In this way, an amorphous polyester resin (A) with an acid value of 12.0 mgKOH / g, a weight average molecular weight of 18000, and a glass transition temperature of 60°C was obtained.

[0128] <Preparation of Colorant-Containing Polyester Resin Particle Dispersion (P1)> The following materials were prepared: Fluorescent colorant (product name: Basic Violet 11:1, Taoka Chemical Co., Ltd.): 2 parts Amorphous polyester resin (A): 200 parts Basic compound: 25% sodium hydroxide solution: 0.4 parts Surfactant: 48.5% sodium dodecyl diphenyl ether disulfonate aqueous solution (product name: Eleminol MON-7, Sanyo Chemical Industries, Ltd.): 4.1 parts Ion-exchanged water (1): 150 parts of ion-exchanged water at 95°C Ion-exchanged water (2): 150 parts of ion-exchanged water at 95°C Ion-exchanged water (3): 150 parts of ion-exchanged water at 95°C

[0129] A twin-screw kneading extruder (model number: TEM26SS, Toshiba Machine Co., Ltd.) was prepared. The barrel of the twin-screw kneading extruder used in this example was made up of a plurality of barrel blocks connected together, and had an overall L / D of 50.

[0130] -Melting process- The barrel temperature of the twin-screw kneading extruder was set to 95°C, and the screw rotation speed was set to 400 rpm. The fluorescent colorant, amorphous polyester resin (A), and 25% sodium hydroxide aqueous solution were fed into the raw material inlet of the twin-screw kneading extruder, and the twin-screw kneading extruder was started. A surfactant was fed from the fourth block barrel, kneaded, and the resin was melted to prepare a mixture.

[0131] -Emulsification process- While operating the twin-screw kneading extruder so that the average feed rate of the mixture was 12 kg / h, ion-exchanged water (1) was fed from the barrel of the 5th block, ion-exchanged water (2) was fed from the barrel of the 7th block, and ion-exchanged water (3) was fed from the barrel of the 9th block, and the mixture was emulsified to obtain a colorant-containing polyester resin particle dispersion (P1). The solid content concentration of the colorant-containing polyester resin particle dispersion (P1) was 31%.

[0132] The particle size distribution of the particles in the colorant-containing polyester resin particle dispersion (P1) was measured using a laser diffraction particle size distribution analyzer (model number: LS13-320, Beckman Coulter). The volume average particle size of the particles in the colorant-containing polyester resin particle dispersion (P1) was 200 nm.

[0133] <Preparation of Colorant-Containing Polyester Resin Particle Dispersions (P2), (P3), (P9) to (P14)> Each colorant-containing polyester resin particle dispersion was prepared in the same manner as in the preparation of colorant-containing polyester resin particle dispersion (P1), except that the specifications and operating conditions of the twin-screw kneading extruder were changed as shown in Table 1. The volume average particle size of the particles in each colorant-containing polyester resin particle dispersion was 200 nm.

[0134] <Preparation of Colorant-Containing Polyester Resin Particle Dispersion (P4)> The following materials were prepared: Organic solvent (1): Ethyl acetate: 40 parts Organic solvent (2): Isopropanol: 25 parts Fluorescent colorant (product name: Basic Violet 11:1, Taoka Chemical Co., Ltd.) :2 parts Amorphous polyester resin (A): 100 parts Basic compound: 10% ammonia water: 11 parts Ion-exchanged water (4): 200 parts of ion-exchanged water at 40°C

[0135] -Dissolution process- Organic solvent (1) and organic solvent (2) were charged into a stirring tank equipped with a stirrer, a condenser, a heater, and a thermometer to prepare a mixed solvent. While stirring and maintaining the temperature in the stirring tank within the range of 35°C to 55°C, the fluorescent colorant and amorphous polyester resin (A) were charged and stirred for 60 minutes to dissolve the fluorescent colorant and resin in the organic solvent.

[0136] -Emulsification process- While maintaining the temperature inside the stirring tank and continuing the stirring, 10% ammonia water was added, and then ion-exchanged water (4) was added dropwise over 90 minutes to emulsify the contents. Heating of the stirring tank was stopped, and the temperature of the emulsion was lowered to room temperature. Thereafter, while maintaining the temperature inside the stirring tank in the range of 40°C to 55°C, the pressure inside the stirring tank was reduced to 10 kPa to remove the organic solvent from the emulsion. The emulsion was passed through a sieve, and 2.1 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (trade name: Eleminol MON-7, Sanyo Chemical Industries, Ltd.) and 30 parts of ion-exchanged water were added to obtain a colorant-containing polyester resin particle dispersion (P4). The colorant-containing polyester resin particle dispersion (P4) had a solids concentration of 31%. The volume average particle size of the particles in the colorant-containing polyester resin particle dispersion (P4) was 200 nm.

[0137] <Preparation of Colorant-Containing Polyester Resin Particle Dispersions (P5) to (P8)> Each colorant-containing polyester resin particle dispersion was prepared in the same manner as in the preparation of the colorant-containing polyester resin particle dispersion (P4), except that the temperature in the emulsification step and the like were changed as shown in Table 1. The volume average particle size of the particles in each colorant-containing polyester resin particle dispersion was 200 nm.

[0138] <Preparation of amorphous polyester resin particle dispersion (1)> The following materials were prepared: Terephthalic acid: 30 parts by mole Fumaric acid: 70 parts by mole Bisphenol A ethylene oxide adduct: 5 mole parts Bisphenol A propylene oxide adduct: 95 parts by mole

[0139] The above materials were charged into a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature of the reaction solution was raised to 220°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature of the reaction solution was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while maintaining the temperature of the reaction solution at 230°C. The temperature of the reactant was then cooled to room temperature. In this way, an amorphous polyester resin with an acid value of 12.0 mgKOH / g, a weight average molecular weight of 18000, and a glass transition temperature of 60°C was obtained.

[0140] A mixed solvent was prepared by adding 40 parts of ethyl acetate and 25 parts of 2-butanol to a vessel equipped with a temperature control means and a nitrogen replacement means. 100 parts of amorphous polyester resin was gradually added to the mixed solvent and dissolved, and 10% aqueous ammonia solution (equivalent to three times the amount by molar ratio relative to the acid value of the resin) was added and stirred for 30 minutes. Next, the inside of the vessel was replaced with dry nitrogen, the temperature of the reaction liquid was kept at 40°C, and 400 parts of ion-exchanged water was dropped at a rate of 2 parts / min while stirring the reaction liquid, and emulsified. After the drop of ion-exchanged water was completed, the temperature of the emulsion was cooled to room temperature (20°C to 25°C), and dry nitrogen was bubbled through the emulsion while stirring for 48 hours, reducing the total amount of ethyl acetate and 2-butanol to 1000 ppm or less. Ion-exchanged water was added to the emulsion to adjust the solid concentration to 20%. In this way, an amorphous polyester resin particle dispersion (1) was obtained. The volume average particle size of the particles in the amorphous polyester resin particle dispersion (1) was 160 nm.

[0141] <Preparation of release agent particle dispersion (1)> The following materials were prepared: Paraffin wax (HNP-9, Nippon Seiro Co., Ltd.): 100 parts Ion-exchanged water: 350 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 1 part

[0142] The above materials were mixed and heated to 100°C, and dispersed using a homogenizer (Ultra Turrax T50, IKA), and then dispersed using a pressure discharge type homogenizer (Manton-Gaulin high pressure homogenizer, Gaulin). When the volume average particle size reached 200 nm, the particles were collected to obtain a release agent particle dispersion (1) with a solid content of 20%.

[0143] <Example 1> [Production of toner particles] The following materials were prepared: Ion-exchanged water: 7 parts Amorphous polyester resin particle dispersion (1): 50 parts Colorant-containing polyester resin particle dispersion (P1): 13 parts Release agent particle dispersion (1): 10 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 1 part

[0144] -First flocculation process- The above materials were placed in a round stainless steel flask, 0.1N nitric acid was added to adjust the pH to 3.5, and 30 parts of a nitric acid aqueous solution with a polyaluminum chloride concentration of 10% was added. The liquid temperature was adjusted to 30°C using an oil bath, and a dispersion treatment was performed using a homogenizer (product name: Ultra Turrax T50, IKA Co., Ltd.). Next, the liquid temperature was raised to 45°C and maintained for 30 minutes to form first aggregated particles.

[0145] -Second coagulation process- While maintaining the temperature of the dispersion containing the first aggregated particles at 45° C., 20 parts of the amorphous polyester resin particle dispersion (1) was added and held for 60 minutes to form second aggregated particles.

[0146] -Combining process- A 0.1N aqueous solution of sodium hydroxide was added to the dispersion liquid containing the second aggregated particles to adjust the pH to 8.5, and the liquid temperature was raised to 84°C and maintained for 150 minutes. The liquid was then cooled to 20°C at a rate of 20°C / min, and the solid matter was filtered off, washed with ion-exchanged water, and dried. The dried matter was sieved to obtain toner particles (1). The volume average particle size of the toner particles (1) was 6.0 μm.

[0147] [Manufacturing of toner with additives] To 100 parts of toner particles (1), 1.5 parts of hydrophobic silica particles (product number: RY50, Nippon Aerosil Co., Ltd.) and 1.0 part of hydrophobic titanium oxide (product number: T805, Nippon Aerosil Co., Ltd.) were added and mixed for 30 seconds at 10,000 rpm using a sample mill. The mixture was then sieved using a vibrating sieve with 45 μm openings to obtain an externally added toner.

[0148] [Manufacturing of developer] 8 parts of the toner with external additives and 92 parts of the following carrier (1) were placed in a V-blender and stirred for 20 minutes, after which the mixture was sieved through a sieve with 212 μm openings to obtain a developer.

[0149] -Manufacture of carrier (1)- 14 parts of toluene, 5 parts of cyclohexyl methacrylate-monoethylaminoethyl methacrylate copolymer (mass ratio 95:5, weight average molecular weight 60000), and 0.2 parts of carbon black (product number: VXC-72, Cabot Corporation) were placed in a sand mill and dispersed to prepare a dispersion liquid. The dispersion liquid and 100 parts of ferrite particles (average particle size 35 μm) were placed in a vacuum degassing kneader, and the mixture was dried under reduced pressure while stirring to obtain a carrier (1).

[0150] <Examples 2 to 12, Comparative Examples 1 to 2> In the same manner as in Example 1, except that the type of colorant-containing polyester resin particle dispersion was changed as shown in Table 1, each toner particle, toner with external additives, and developer were prepared.

[0151] <Performance evaluation> [Image density unevenness] The following operations and image formation were carried out in an environment with a temperature of 23°C and a relative humidity of 70%. The lower the dispersibility of the colorant inside the toner particles, the greater the concern about charge leakage due to the low dispersibility of the colorant. Images were formed under slightly higher humidity conditions where image density unevenness due to charge leakage is more likely to occur. An ApeosPortIV C4470 (FUJIFILM Business Innovation Co., Ltd.) was prepared as an image forming apparatus for forming an image for evaluation. A developer was placed in the developing device, and a replenishment toner (the same toner as that contained in the developer) was placed in the toner cartridge. A4 size OS coated paper (grammage 127g / m 2 One hundred images with an image density of 30% were output onto a printer (FUJIFILM Business Innovation Co., Ltd.). The image density was measured at ten random points on the 100th sheet using a densitometer (X-Rite938, X-Rite). The difference between the maximum and minimum image densities at the ten points (image density difference) was calculated, and the image density difference was classified as follows. The results are shown in Table 1. A: Image density difference is 0.20 or less B: Image density difference is more than 0.20 and 0.25 or less C: Image density difference is more than 0.25 and less than 0.30 D: Image density difference is more than 0.30

[0152] [Heat storage] 2 g of the toner containing the additive was stored for 10 hours in an environment with a temperature of 55° C. and a relative humidity of 50%. After storage, the toner containing the additive was visually observed and classified as follows. The results are shown in Table 1. A: No aggregates were observed. B: A small amount of agglomerates is present. C: Almost the entire part is aggregated.

[0153] [Table 1]

[0154] The method for producing a toner for developing electrostatic images according to the present disclosure includes the following aspects. (((1))) A method for producing a toner for developing an electrostatic image, comprising agglomerating and coalescing material particles including colorant-containing polyester resin particles in a dispersion medium to obtain toner particles, The colorant-containing polyester resin particles are produced the step of producing the colorant-containing polyester resin particles includes mixing a basic colorant and a polyester resin while applying heat to obtain a mixture, and emulsifying the mixture, In the production process of the colorant-containing polyester resin particles, a time-weighted average T°C of the temperature of the polyester resin and a time R seconds during which the temperature of the polyester resin is in the range of 35°C or more and 100°C or less satisfy the relationship of 200≦(T×lnR)≦550. A method for producing a toner for developing electrostatic images. (((2))) The method for producing a toner for developing electrostatic images according to (((1))), wherein the temperature of the polyester resin is in the range of 35° C. or more and 100° C. or less throughout the entire process of producing the colorant-containing polyester resin particles. (((3))) The method for producing a toner for developing electrostatic images according to ((1))) or (((2))), wherein no organic solvent is used in the process for producing the colorant-containing polyester resin particles. (((4))) The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((3))), wherein the basic colorant contains a basic dye. (((5))) The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((4))), wherein the polyester resin contains a non-crystalline polyester resin. (((6))) The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((5))), wherein a mass ratio of the basic colorant and the polyester resin contained in the colorant-containing polyester resin particles is basic colorant:polyester resin=0.1:99.9 to 20:80. (((7))) The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((6))), wherein the colorant-containing polyester resin particles have a volume average particle size of 50 nm or more and 500 nm or less.

[0155] According to (((1))), (((2))), (((3))), (((4))), (((5)), (((6))) or (((7))), a production method is provided for producing a toner for developing electrostatic images, which suppresses the occurrence of uneven image density and has excellent heat storage properties, as compared to when the value of 200≦(T×lnR) is less than 200 or exceeds 550.

Claims

1. A method for producing a toner for developing an electrostatic image, comprising agglomerating and coalescing material particles including colorant-containing polyester resin particles in a dispersion medium to obtain toner particles, The colorant-containing polyester resin particles are produced the step of producing the colorant-containing polyester resin particles includes mixing a basic colorant and a polyester resin while applying heat to obtain a mixture, and emulsifying the mixture, In the production process of the colorant-containing polyester resin particles, a time-weighted average T°C of the temperature of the polyester resin and a time R seconds during which the temperature of the polyester resin is in the range of 35°C or more and 100°C or less satisfy the relationship: 200≦(T×lnR)≦550. A method for producing a toner for developing electrostatic images.

2. 2. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the temperature of the polyester resin is in the range of 35° C. or more and 100° C. or less throughout the entire process of producing the colorant-containing polyester resin particles.

3. 2. The method for producing a toner for developing electrostatic images according to claim 1, wherein no organic solvent is used in the process for producing the colorant-containing polyester resin particles.

4. The method for producing a toner for developing electrostatic images according to claim 1 , wherein the basic colorant comprises a basic dye.

5. The method for producing a toner for developing electrostatic images according to claim 1 , wherein the polyester resin comprises an amorphous polyester resin.

6. 2. The method for producing a toner for developing electrostatic images according to claim 1, wherein a mass ratio of the basic colorant and the polyester resin contained in the colorant-containing polyester resin particles is basic colorant:polyester resin=0.1:99.9 to 20:

80.

7. 2. The method for producing a toner for developing electrostatic images according to claim 1, wherein the colorant-containing polyester resin particles have a volume average particle size of 50 nm or more and 500 nm or less.

Citation Information

Patent Citations

  • Emulsion composition and water-based ink

    JP2004010846A

  • Method for manufacturing toner

    JP2010276750A

  • Resin fine particle, thermoplastic resin particle, and method for producing resin fine particle

    JP2021127428A